Analisis Aspek Farmakokinetika Klinik Pasien Gagal Ginjal pada Irna Penyakit dalam RSUP Dr. M. Djamil Padang - Lucida, Henny; Trisnawati, Riah; Suardi, Muslim (Fakultas Farmasi Universitas Andalas, 2011)
A study on the evaluation of clinical pharmacokinetic aspect to in-patient with renal failure at internal Ward Dr. M. Djamil hospital Padang has been conducted. The aspect studied was dosage individualization bades on patientâs patophysiological condition. The study aimed at comparing the dosage regimen given to the renal failure patient with that calculated using pharmacokinetic equations. This study was observasionaly prospective by using cross-sectional method. In the period of June â September 2010, 48 renal failure patients includes in inclusion criterion. Results showed that medications which mainly renal excreted or potentially nephrotoxic given to patients are ciprofloxacin, digoxin, ranitidin, metformin, captopril, furosemide and hydrochlortiazide. Patients treated with those medications were evaluated in terms of dosage regimens and clinical response. There were 4 cases of higher dose than recommended included 1 of 8 cases of captopril use, 2 of 9 cases of ciprofloxacin use and 1 of case of metformin use. It uses also found that hydrochlortiazide which should be avoided to patients with Clcr < 30 ml/min (4 cases)